Contribution of connectivity metrics to the assessment of biodiversity – Some methodological considerations to improve landscape planning. (November 2018) - Pietsch, Matthias
Abstract: Land use change and the resulting physical and functional disconnection of ecological networks are some of the driving forces of biodiversity loss. Landscape planning and environmental assessments are essential instruments for addressing such problems. Methods for quantifying and predicting the impacts of fragmentation on biodiversity are needed, as are methods for deriving objectives and measures in the landscape planning process. While a number of different methodologies regarding network analysis and graph theory provide tools and methods for analyzing ecological networks, graph theory is a tool that may be helpful for reducing negative ecological impacts and finding appropriate solutions in the landscape planning process. These methods can be used as evaluation tools in the planning process, to analyze and visualize different possible scenarios for the participation process, or to define areas that are most important for measures to preserve or enhance biodiversity. Using the example of three target species in Saxony, the use of the Probability of Connectivity Index (PC) as a functional connectivity index for potential connectivity analysis is examined. Implementation and requirements for the planning process are described.